\(\Leftrightarrow x-1-2\sqrt{x-2}=x+5+4\sqrt{x-2}\)
\(\Leftrightarrow-6\sqrt{x-2}=5+1=6\left(loại\right)\)
\(\Leftrightarrow x-1-2\sqrt{x-2}=x+5+4\sqrt{x-2}\)
\(\Leftrightarrow-6\sqrt{x-2}=5+1=6\left(loại\right)\)
1. Giải phương trình: \(\sqrt{x-2}+\sqrt{4-x}=\sqrt{2}\) .
2. Giải phương trình: \(4x^4-7x^3+9x^2-10x+4=0\).
3. Giải hệ phương trình: \(\left\{{}\begin{matrix}x^2+y^2=3-xy\\x^4+y^4=2\end{matrix}\right.\) .
giải phương trình
1)\(\sqrt{9\left(x-1\right)}=21\)
2)\(\sqrt{1-x}+\sqrt{4-4x}-\dfrac{1}{3}\sqrt{16-16x}+5=0\)
3)\(\sqrt{2x}-\sqrt{50}=0\)
4)\(\sqrt{4x^2+4x+1}=6\)
5)\(\sqrt{\left(x-3\right)^2}=3-x\)
1.Giải phương trình:
\(\sqrt{x^2-4}-x^2+4=0\)
2.Giải phương trình:
\(\sqrt{x^2-4x+5}+\sqrt{x^2-4x+8}+\sqrt{x^2-4x+9}=3+\sqrt{5}\)
Giải các phương trình sau :
1/\(\sqrt{x+2+4\sqrt{x-2}}=5\)
2/\(\sqrt{x+3+4\sqrt{x-1}}=2\)
3/\(\sqrt{x+\sqrt{2x-1}}=\sqrt{2}\)
4/\(\sqrt{x-2+\sqrt{2x-5}}=3\sqrt{2}\)
Bài 1. Giải các phương trình sau:
1) \(\sqrt{2x-1}=\sqrt{5}\) 2) \(\sqrt{x-5}=3\) 3) \(\sqrt{9\left(x-1\right)}=21\) 4) \(\sqrt{2}x-\sqrt{50}=0\)
Giải các phương trình sau
a)\(x^2-2-x+\sqrt{2}=0\)
b) \((1-\sqrt{2})x^2-2(1+\sqrt{2})x+1+3\sqrt{2}=0\)
Giải các phương trình sau:
a \(x^2-11=0\)
b \(x^2-12x+52=0\)
c \(x^2-3x-28=0\)
d \(x^2-11x+38=0\)
e \(6x^2+71x+175=0\)
f \(x^2-\left(\sqrt{2}+\sqrt{8}\right)x+4=0\)
g\(\left(1+\sqrt{3}\right)x^2-\left(2\sqrt{3}+1\right)x+\sqrt{3}=0\)
Bài 2. Giải các phương trình sau. a) 3x - 2sqrt(x - 1) = 4 b) sqrt(4x + 1) - sqrt(x + 2) = sqrt(3 - x) c) (sqrt(x - 1) - sqrt(5 - x))(|10 - x| + 2x - 16) = 0
giải phương trình sau:
a) \(4x^2+\left(8x-4\right).\sqrt{x}-1=3x+2\sqrt{2x^2+5x-3}\)
b) \(8x^3-36x^2+\left(1-3x\right)\sqrt{3x-2}-3\sqrt{3x-2}+63x-32=0\)
c) \(2\sqrt[3]{3x-2}-3\sqrt{6-5x}+16=0\)
d) \(\sqrt[3]{x+6}-2\sqrt{x-1}=4-x^2\)
Câu 2: Giải các phương trình sau:
a. \(\sqrt{4x-8}\) - \(\sqrt{x-2}\) - 4 + \(\dfrac{1}{3}\)\(\sqrt{9x-18}\)
b. \(\sqrt{x^2-6x+9}\) - \(\dfrac{\sqrt{6+\sqrt{3}}}{\sqrt{2}+1}\)=0